PENGATURAN SUDUT AZIMUTH ROKET RUM UNTUK OPERASI PELUNCURAN PADA KECEPATAN ANGIN DI ATAS 10 KNOT (AZIMUTH ANGLE’S SETTING OF ROCKET RUM FOR LAUNCH OPERATION AT WIND SPEED MORE THAN 10 KNOT) - Heri Budi Wibowo; Ahmad Riyadl; Yudha Agung Nugroho (Jurnal Teknologi Dirgantara, 2016)
RUM rocket is a rocket used in the payload competition among university students. The rocket is designed to bring a maximum payload of 1 kg to altitude of 600-1000 m and falls safely on a 500 m radius of the left and right rear of the center point of the launching pad of the conditions of wind speeds below 10 knots. In extreme circumstances where the wind speed is above 10 knots, the effect of speed and direction of wind to the stability of the rocket flight direction large enough to cause it to fall beyond the defined safety radius. The research aims to adjust azimuth setting of the rocket so that the fall of the rocket motor remains secure within the radius of the launch area. The study was conducted by testing a rocket RUM in extreme conditions (wind speed of 10-20 knots) with variations in shear-pin and azimuth angle. The test variables are the position of the fallen rocket motor. The results show that the wind direction and speed significantly affecting direction of rockets flight. The results show that rocket azimuth angle of 60 degrees with the direction of 90 degrees from the wind direction can make thea rocket falls on a secure area (within 500 m). ABSTRAKRoket RUM adalah roket untuk lomba muatan antar mahasiswa. Roket didisain membawa beban maksimum 1 kg dengan ketinggian 600-1000 m dan jatuh pada radius 500 m dari titik pusat peluncuran dengan kondisi kecepatan angin di bawah 10 knot. Dalam keadaan ekstrim dimana kecepatan angin di atas 10 knot, pengaruh kecepatan angin terhadap arah terbang roket menjadi besar sehingga dapat menyebabkan jatuhnya roket meleset di luar radius aman yang telah diitetapkan. Penelitian ini bertujuan mengatur sudut azimuth roket untuk mengatur jatuhnya motor roket sehingga tetap aman dalam radius area peluncuran. Penelitian dilakukan dengan melakukan pengujian roket RUM pada kondisi ekstrim (kecepatan angin 10-20 knot) dengan variasi penahan beban dan sudut azimuth. Hasil optimasi menunjukkan bahwa dengan menggunakan penahan beban dan pengaturan sudut azimuth roket 60 derajat dengan arah 90 derajat dari arah angin dapat membuat roket jatuh pada daerah aman peluncuran (500 m).